Comparative Study of the Effects of Sublingual Trinitroglycerin and Sublingual Misoprostol on Cervical Preparation before Hysteroscopy: A Randomized Controlled Trial - Shahla Mirgaloybayat; Mahmoodreza Madadian; Kobra Tahermanesh; Roya Derakhshan; Saeedeh Sarhadi; Samaneh Rokhgireh (IMR Press, 2024)
Background: Hysteroscopy is a valuable surgical technique, but some complications are related to cervical dilatation. Sublingual trinitroglycerin (TNG) is a vasodilator that can facilitate cervical dilation. In our study, we compared its effectiveness to that of misoprostol. Methods: This randomized controlled trial study was conducted on 199 women of reproductive age who were referred to Rasoul Akram Hospital. Patients were randomly divided into two groups: TNG and misoprostol. Next, they were examined for clinical and practical indicators of cervical preparation. The data was analyzed using SPSS software. Results: Demographic characteristics exhibited no significant differences between the groups. The mean size of the largest dilator inserted without resistance showed not statistically significant difference between the TNG and misoprostol groups (6.26 ± 1.95 vs. 6.57 ± 2.05; p = 0.20). Side effects were reported in 66 (33.2%) of the women studied. The misoprostol group experienced a significantly higher rate of side effects (53.7%) compared to the TNG group (14.4%; p < 0.001). The most frequently observed side effect in the TNG group was headache, which occurred at a statistically significantly higher rate than in the misoprostol group (p = 0.04). On the other hand, uterine bleeding before hysteroscopy was significantly lower in the TNG group compared to the misoprostol group (p < 0.001). Conclusions: There was no statistically significant difference in the mean size of the largest dilator inserted without resistance between the TNG and misoprostol groups. Additionally, TNG experienced significantly fewer side effects than sublingual misoprostol group, with headache being the most prominent side effect. Sublingual TNG can be used to improve cervical preparation before hysteroscopy. Clinical Trial Registration: The study has been registered on https://trialsearch.who.int/Trial2.aspx?TrialID=IRCT20191123045476N4 (registration number: IRCT20191123045476N4).